Customer satisfaction towards broadband of Telekom Malaysia - Wong, Chiung Kiet (Universiti Malaysia Sarawak (UNIMAS), 2013)
Customer satisfaction is well known among service provider sectors in the last three decades. Many companies have adopted and implemented it as a high priority operational goal in order to expand their business.